An articulated robotic forceps design with a parallel wrist-gripper mechanism and parasitic motion compensation - TÜMERDEM, UĞUR (My University, 2022)
In this paper, a novel four degrees-of-freedom (4DOF) articulated parallel forceps mechanism with a large orientation workspace (⁠±90deg in pitch and yaw, 360deg in roll rotations) is presented for robotic minimally invasive surgery. The proposed 3RSR-1UUP parallel mechanism utilizes a UUP center leg that can convert thrust motion of the 3RSR mechanism into gripping motion. This design eliminates the need for an additional gripper actuator, but also introduces the problem of unintentional gripper opening/closing due to parasitic motion of the 3RSR mechanism. Here, position kinematics of the proposed mechanism, including the workspace, is analyzed in detail, and a solution to the parasitic motion problem is provided. Human-in-the-loop simulations with a haptic interface are also performed to confirm the feasibility of the proposed design.
Keywords: Makina Mühendisliği; Makina Teorisi ve Dinamiği; Mühendislik ve Teknoloji; Mechanical Engineering; Machine Theory and Dynamics; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Mühendislik; MÜHENDİSLİK, MEKANİK; Engineering, Computing & Technology (ENG); ENGINEERING; ENGINEERING, MECHANICAL; Otomotiv Mühendisliği; Makine Mühendisliği; Hesaplamalı Mekanik; Fizik Bilimleri; Automotive Engineering; Computational Mechanics; Physical Sciences; kinematics; manipulator theory; mechanism theory; medical and bio design of mechanisms and robotics; parallel manipulators; parallel robots; robot design; robot kinematics; robotic systems; simulation-based design